2023
DOI: 10.1002/glr2.12056
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield stability analysis using parametric and nonparametric statistics in oat (Avena sativa L.) genotypes in Ethiopia

Gezahagn Kebede,
Walelign Worku,
Habte Jifar
et al.

Abstract: BackgroundThe performance of oat genotypes differs across environments due to variations in biotic and abiotic factors. Thus, evaluation of oat genotypes across diverse environments is very important to identify superior and stable genotypes for yield improvement.MethodsThe study aimed to assess the interaction (genotype‐by‐environment interaction; GEI) effect and determine the stability of grain yield in oat (Avena sativa L.) genotypes in Ethiopia using parametric and nonparametric stability statistics. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The selection of high-yielding varieties using a single stability measurement was considered inaccurate, so it is necessary to combine various stability measurements [14]. Various studies have reported the combined stability measurements, including those of black soybeans [26,27], durum wheat [28,29], sweet potatoes [30], stevia [31], and rice [32]. In combining stability measurements, biplot visualization is very important to use.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of high-yielding varieties using a single stability measurement was considered inaccurate, so it is necessary to combine various stability measurements [14]. Various studies have reported the combined stability measurements, including those of black soybeans [26,27], durum wheat [28,29], sweet potatoes [30], stevia [31], and rice [32]. In combining stability measurements, biplot visualization is very important to use.…”
Section: Introductionmentioning
confidence: 99%
“…Several other empirical results exist for crops not covered in our analysis, e.g., for oats in Ethiopia (Kebede et al 2023), for chickpeas in India (Kumar et al 2020), energy crops in the EU (Popp et al 2021), maize in several locations (Kang 1993), and cereals and vegetables in Europe and North America Hollósy 2019a, 2019b), using various methods for evaluating yield stability, but all agree that both climate impacts and the impacts of management decisions regarding farming technology interact in creating actual yield fluctuations. Shojaei et al (2021) used the AMMI methodology for maize in Iran, comparing 12 maize hybrids under different environmental conditions for a two-year study using similar stability measures as Bose et al (2014).…”
Section: Discussionmentioning
confidence: 58%
“…This was based on stability factors such as lower values of Wi 2 , σ 2i , P i , and s 2 di, a high BLUP factor, and bi equal to 1. The use of different parametric stability assessments has also been reported in wheat (Bornhofen et al, 2017), rice (Lee et al, 2023), safflower (Afzal et al, 2021), and oat (Kebede et al, 2023).…”
Section: Discussionmentioning
confidence: 99%